2008
DOI: 10.1080/00048670701881553
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pro Re Nata Medications in Acute Inpatient Care

Abstract: PRN medication use has endured as standard practice and the results of the present study are consistent with the reported frequency of use increasing slightly over the years. The combination of second-generation antipsychotics as regular medications and benzodiazepines for PRN medication is consistent with recommended treatment guidelines. The small subset of patients who were overrepresented in the PRN administrations is noteworthy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 22 publications
2
55
1
Order By: Relevance
“…PRN medication use has increased as standard practice in acute patient care, but in recent studies a poor documentation of prescription and administration of these drugs was found [11,18]. In our study, we used a patient data management system, which has been established a longer time ago and all the intensive care staff were strictly committed …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PRN medication use has increased as standard practice in acute patient care, but in recent studies a poor documentation of prescription and administration of these drugs was found [11,18]. In our study, we used a patient data management system, which has been established a longer time ago and all the intensive care staff were strictly committed …”
Section: Discussionmentioning
confidence: 99%
“…Antiemetics, cathartic medicine, analgosedatives and blood pressure medication are often prescribed on a 'pro re nata' (PRN) or 'as needed' basis. In these cases, time points of prescription, doses and frequencies are not scheduled but can be individually adjusted to the patient's needs [9][10][11]. The 'need for medication' may be expressed verbally or nonverbally by the patient, depending on his/her condition, or identified via assessments by the caretaker [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This responsibility rests solely on the nursing staff and their ability to use autonomous clinical decision-making to distinguish between different behaviors associated with those conditions prior to the administration of PRN medication (Hilton & Whiteford, 2008;Usher et al, 2009). Approximately 75% of hospital psychiatric patients receive PRN medications and there are presently few studies that explore nurses' rationale for the decision-making processes when administrating those medications (Stein-Parbury, Reid, Smith, Mouhanna, & Lamont, 2008;Usher et al, 2009;Winship, 2010).…”
Section: Background and Statement Of The Problemmentioning
confidence: 99%